Rare genetic variants and the risk of cancer. - Bodmer, W; Tomlinson, I (2010)
There are good reasons to expect that common genetic variants do not explain all of the inherited risk of the common cancers, not least of these being the relatively low proportion of familial relative risk that common cancer SNPs currently explain. One promising source of the unexplained risk is rare, low-penetrance genetic variants, a class that ranges from low-frequency polymorphisms (allele frequency < 5%) through subpolymorphic variants (frequency 0.1-1.0%) to very low frequency or 'private' variants with frequencies of 0.1% or less. Examples of rare cancer variants include breast cancer susceptibility loci CHEK2, BRIP1 and PALB2. There are considerable challenges associated with the discovery and testing of rare predisposition alleles, many of which are illustrated by the issues associated with variants of unknown significance in the Mendelian cancer predisposition genes. However, whilst cost constraints remain, the technological barriers to rare variant discovery and large-scale genotyping no longer exist. If each individual carries many disease-causing rare variants, the so-called missing heritability of cancer might largely be explained. Whether or not rare variants do end up filling the heritability gap, it is imperative to look for them along side common variants.